2020
DOI: 10.3389/fendo.2020.601956
|View full text |Cite
|
Sign up to set email alerts
|

Does Maternal Normal Range Thyroid Function Play a Role in Offspring Birth Weight? Evidence From a Mendelian Randomization Analysis

Abstract: Background The association between normal range thyroid function and offspring birth weight has been postulated, but evidence from observational studies is prone to be confounded. We conducted a two-sample Mendelian randomization (MR) study to explore the causal effects of maternal thyroid stimulating hormone (TSH) and free thyroxine (FT4) on birth weight. Methods We utilized public shared summary-level statistics from European-ancestry genome wide association studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Nonetheless, we cannot exclude the possibility that thyroid dysfunction and autoimmunity may contribute to other adverse outcomes. Consistent with a previous MR study[44], we also did not identify an MR association between maternal TSH levels within the reference range and birth weight. Notably, our MR analyses provide evidence suggesting that maternal TSH levels during pregnancy may potentially influence gestational duration, although the effect may be nonlinear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, we cannot exclude the possibility that thyroid dysfunction and autoimmunity may contribute to other adverse outcomes. Consistent with a previous MR study[44], we also did not identify an MR association between maternal TSH levels within the reference range and birth weight. Notably, our MR analyses provide evidence suggesting that maternal TSH levels during pregnancy may potentially influence gestational duration, although the effect may be nonlinear.…”
Section: Discussionsupporting
confidence: 90%
“…High-quality Mendelian randomization studies in clinical thyroidology are deemed crucial for gaining valuable insights into the relationship between thyroid functions and birth outcomes[43]. However, to date, only one MR study has explored the causal effect of TSH and FT4 levels within the normal range on birth weight and did not identify statistically significant causal associations [44].…”
Section: Resultsmentioning
confidence: 99%
“…Euthyroidism is essential for establishing and maintaining a healthy pregnancy. Although the relationships between TSH levels and various adverse perinatal outcomes have been reported, conclusions are inconsistent 2,4,15,21–23 . A nested prospective cohort study observed a positive linear relationship between log‐transformed maternal TSH levels and the risk of subsequent child loss 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Another meta‐analysis reported a tendency toward an increased risk of LGA among hypothyroid mothers 3 . Recently a two‐sample Mendelian randomization study did not identify any causality between normal‐range thyroid function and offspring birth weight 21 . In the present study, a positive association was shown between increased TSH levels with SGA when TSH level was between 1.5 and 3.5 mIU/L, and elevated preconception TSH level, >4.20 or >2.50 mIU/L (Figure S1) was associated with a higher risk of SGA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation